Music and driving game performance - North, Adrian; Hargreaves, David (Wiley-Blackwell Publishing Ltd., 1999)
This study investigated the effects of the nature of music and a concurrent task on measures of task performance and musical preference. Subjects completed 5 laps of a computer motor racing game whilst listening to either arousing or relatively unarousing music in either the presence or absence of a backward-counting task. Both these manipulations affected performance on the game with arousing music and backward-counting leading to slower lap times than relatively unarousing music and the absence of the backward-counting task. Backward-counting led to lower liking for the music than did the absence of this task. These results support the idea that music and the concurrent task competed for a limited processing resource. The results also indicated that liking for the music was positively related to task performance, and in conjunction these findings seem to suggest a direct link between music and the listening context.